2019
DOI: 10.1016/j.healun.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Third Annual Report From the ISHLT Mechanically Assisted Circulatory Support Registry: A comparison of centrifugal and axial continuous-flow left ventricular assist devices

Abstract: BACKGROUND:The IMACS Registry compiles and analyzes worldwide data from patients undergoing implantation of durable left ventricular assist devices. METHODS: Data encompassing 16,286 LVAD recipients from 4 collectives and 24 individual hospitals was collected and analyzed. In this 3rd annual report we compare and contrast outcomes, adverse events and risks factors between axial flow and centrifugal flow device recipients. RESULTS: Significant differences were found in the baseline characteristics of axial vs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
180
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(194 citation statements)
references
References 7 publications
14
180
0
Order By: Relevance
“…As mentioned previously, the literature is currently unclear about the long‐term effects of preoperative VAD support in HTx patients . In general, the VAD support time before HTx has been shorter in American patients than in European cohorts in publications to date, and the support duration might have been a relevant factor for these effects . Different studies reported adverse effects of prolonged VAD support time before HTx .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, the literature is currently unclear about the long‐term effects of preoperative VAD support in HTx patients . In general, the VAD support time before HTx has been shorter in American patients than in European cohorts in publications to date, and the support duration might have been a relevant factor for these effects . Different studies reported adverse effects of prolonged VAD support time before HTx .…”
Section: Discussionmentioning
confidence: 99%
“…As this disease progresses, pharmacological therapies may fail, and current guidelines recommend orthotopic heart transplantation (HTx) as the gold standard of care . As donor organs are quite rare, circulatory assistance with implanted ventricular assist devices (VADs) is often needed as a bridge to transplant therapy . Although assist devices have substantially improved in recent years, there are still various complications, such as bleeding and severe infections, which limit the median survival time of patients with VADs to approximately 2 to 5 years, depending on individual risk profiles and device configurations .…”
Section: Introductionmentioning
confidence: 99%
“…Analyzed J-MACS data have been uploaded on the biannual basis on the home page of the Japanese Association for Thoracic Surgery (https ://www.jpats .org/) since Oct 2018. Similar to INTERMACS [2] and IMACS [3], we have decided to publish annual report of J-MACS, and this is the second official report of J-MACS, which includes data as of Oct 30, 2018. The cut-off date for data collection of this report was Dec 31, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke remains a devastating complication of left ventricular assist device (LVAD) therapy and a leading cause of death during LVAD support . LVAD patients who experience a stroke have decreased life expectancy and diminished quality of life; those who are transplant candidates see a significant reduction in their chances of receiving a heart transplant …”
Section: Introductionmentioning
confidence: 99%